Frogfishes : Biodiversity, Zoogeography, and Behavioral Ecology - Pietsch, Theodore W. (Book collections on Project MUSE., 2020)
Unique among the world's fishes, frogfishes display a bizarre combination of attributes and behaviors that make them a subject of fervent study. Through cunning and trickery, they turn would-be predators into prey; they "walk" across the ocean floor and jet-propel through open water; some lay their eggs in a floating mucoid mass, while others employ complex patterns of parental care; and they are certainly among the most colorful of nature's productions. In Frogfishes, two of the world's leading anglerfish experts, Theodore W. Pietsch and Rachel J. Arnold, bring together an enormous amount of information about these incredible creatures. The only detailed exploration of frogfishes in print, the book touches on everything from their morphology and biomechanics to their diets and habitats. Enhanced with more than 500 spectacular color images, the book also includes * a thorough look at about 5,000 preserved specimens; * an annotated synonymy for all extant taxa, as well as keys and tables to facilitate identification; * insights into frogfish feeding, locomotion, mimicry, and reproductive behavior; * descriptions of recent scientific advances, including the discovery of new species, shifts in geographic distribution, and emerging DNA sequencing techniques; and * tips for frogfish-seeking divers and aquarists that emphasize conservation. Unmasking the mysteries of frogfish evolution and phylogenetic relationships through close examination of their fossil record, morphology, and molecular reconstruction, Frogfishes demonstrates the surprising diversity and beauty of this remarkable assemblage of marine shorefishes